Pengaruh Pendidikan Kesehatan Tentang Pernikahan Dini Melalui Media Komik Digital Technique Terhadap Pengetahuan dan Sikap Siswa - Netti Herawati; Murdaya Murdaya; Dianita Indriani; Ajeng Galuh Wuryandari (NHM PRESS, 2023)
This research aims to determine the effect of health education about early marriage through digital comic technique media on the knowledge and attitudes of high school students. This research method is quantitative research using a pretest posttest with control group design with the type of intervention using digital comic techniques in the intervention group. The results of the paired ttest analysis, the knowledge aspect is known to be p-value =p=0.000(p < 0.05), while attitude is 0.000 (p < 0.05). In conclusion, health education using digital comic techniques has been proven to increase high school students' knowledge and attitudes about early marriage. The results of the independent test show that the significance level for the knowledge aspect is 0.51 (significance > 0.05) and the significance level for the attitude aspect is 0.55 (> 0.05). These two intervention groups did not provide a significant difference in knowledge and attitudes. students about early marriage